Phytochemicals: Potential in Management of Climacteric Neurobiology - Chopra, Kanwaljit; Bansal, Seema; Kamal Sachdeva, Anand (Current Pharmaceutical Design, 2016)
Menopause jeopardizes the integrity of brain and makes it vulnerable to various diseases, both of psychiatric and degenerative nature. Exogenous estrogen supplementation confers neuroprotection but the results of Women's Health Initiative (WHI), Million Women Study (MWS) and incidence of endometrial cancer, breast cancer and venous thromboembolism reported with estrogen use have engendered doubts over its clinical translation for postmenopausal neurological disorders. Scientific community and general public have started recognizing the protective potential of phytochemicals in climacteric medicine. These phytochemicals are plant-derived, non-steroidal bioactive estrogenic compounds. Emerging preclinical studies have suggested that these phytochemicals display potential benefits in mitigating postmenopausal depression, anxiety, cerebral ischemia and cognitive dysfunction. Thus, the aim of present review is: a) to give an overview of neuroprotective action of estrogen, b) to address the chemical and pharmacological features of various classes of phytoestrogens, and c) to present preclinical and clinical evidence of effect of phytoestrogens on climacteric neurobiology with their possible mechanisms of action.
Keywords: Phytochemicals